2018
DOI: 10.1007/s10549-018-5000-y
|View full text |Cite
|
Sign up to set email alerts
|

High patient satisfaction with a simplified BRCA1/2 testing procedure: long-term results of a prospective study

Abstract: Purpose In the BRCAsearch study, unselected breast cancer patients were prospectively offered germline BRCA1 / 2 mutation testing through a simplified testing procedure. The purpose of the present study was to evaluate satisfaction with the BRCAsearch testing procedure and, furthermore, to report on uptake rates of prophylactic surgeries among mutation carriers. Methods Pre-test information was provided by a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It is reassuring that we, and others, have found that patients with cancer are supportive of this testing model. 29,30,31,32,33,34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reassuring that we, and others, have found that patients with cancer are supportive of this testing model. 29,30,31,32,33,34…”
Section: Discussionmentioning
confidence: 99%
“…7 Many other centers have adopted similar processes, with comparable positive results. 30,31,32,33,34 Herein we report on the development and evaluation of simple, cancer-based eligibility criteria for use in mainstream genetic testing in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Different mainstream models of integrating BRCA testing into the breast cancer pathway have been implemented internationally with great success and high levels of patient and clinician satisfaction . In the United Kingdom, the Mainstreaming Cancer Genetics programme ran from 2013 to 2018 and included testing at diagnosis for young onset (≤45), triple negative, two primary breast cancers ≤60, male breast cancer, or breast cancer plus a first degree relative with breast cancer .…”
Section: How Does Genomic Testing Inform Treatment Pathways For Commomentioning
confidence: 99%
“…Different mainstream models of integrating BRCA testing into the breast cancer pathway have been implemented internationally with great success and high levels of patient and clinician satisfaction. [14][15][16][17][18] In the United Kingdom, the Mainstreaming Cancer Genetics programme ran from 2013 to 2018 and included testing at diagnosis for young onset (≤45), triple negative, two primary breast cancers ≤60, male breast cancer, or breast cancer plus a first degree relative with breast cancer. 16 It is predicted that if the United Kingdom adopted the MCG breast cancer mainstream testing guidelines, this would result in 2500 BRCA mutations identified per year and find all BRCA mutations from testing only a third of breast cancer patients most likely to carry a mutation.…”
Section: Breast Cancermentioning
confidence: 99%
“…Though traditional pre‐ and post‐genetic counseling has been shown to improve knowledge related to single gene, or specific cancer syndromes, some studies report that cancer genetic knowledge remains suboptimal even after counseling (Scherr, Christie, & Vadaparampil, 2016). Alternative models of genetic counseling, through telegenetics, or streamlined models have been demonstrated to be acceptable by patients in some settings (Nilsson et al, 2019). Variations in outcomes may exist between different racial and ethnic groups (Hann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%